PENDAMPINGAN MASYARAKAT DESA LANGKO DALAM PEMBUATAN LEGALITAS PRODUK JAJANAN RINGAN - Ilhamdani, yusril; Rahmadani, Baiq Kirana Putri; Herlina, Hawari; Assegaf, Ali; Wulandari, Raden Roro; Febriyant, Aluh Fatimah Nadya; Ningsih, Baiq Apna Askuri; Yasa, I Dewa Gede Purna; Lestari, Dini Istiayu; Sukma, Wanda Matari (Jurnal Wicara, 2023)
This study presents the findings of a community service program conducted in Langko Village with the goal of improving UMKM through product legality initiatives. Our 45-day intervention aimed to alleviate the difficulties faced by UMKM owners in the Langko Lauq and Langko Bat hamlets. In collaboration with the PLUT, the program included the creation of compliant product labels as well as the acquisition of NIB and SPP-IRT. Targeted socialization efforts also emphasized the importance of product legality and included expert-led sessions on financial literacy and digital marketing. Our intervention resulted in a remarkable transformation of the UMKM landscape of Langko Village. UMKM owners successfully obtained product legality documentation through streamlined procedures and expert guidance, fostering consumer trust and expanding market reach. Participants responded positively to the socialization efforts, which promoted informed decision-making and business diversification. Finally, the community service program demonstrated the tangible benefits of providing UMKM owners with legal recognition and comprehensive knowledge. The integration of product legality and strategic socialization can serve as a model for fostering long-term economic growth in rural communities. This research illuminates the potential of collaborative initiatives to boost local entrepreneurship.